Developing computational and experimental models of heat transfer through multi-layered textile structures - Nguyen, Ngoc Son; Nguyen, Dinh Phuong; Do, Xuan Doanh; Tong, Minh Hoa; Nguyen, Anh Tuan; Nguyen, Manh Thang (Communications in Physics, 2024)
Object signature management is a critical and urgent task that helps conceal and restrict the detection of contemporary optoelectronic systems. The design of thermal camouflage textiles and material solutions constitute a significant scientific area, however publications in this area are restricted because of military competitiveness and technological secrecy. Research on thermal camouflage materials has drawn interest both domestically and internationally for a variety of purposes, especially in military applications. Multi-layered Textile Structures (MTS) is a material with several advantages, such as its simple structure, capacity to combine many different materials with many different qualities, and great applicability. The article includes a model of computation and simulation of heat transfer through multi-layer textiles, as well as tests to assess the heat shielding effect and heat radiation energy of some samples of multi-layer textiles made of domestic materials. The initial computational and experimental results constitute an important foundation for further research and application of multi-layered textile structures.